Speaking up: a model of self-advocacy for STEM undergraduates with ADHD and/or specific learning disabilities - Mariel A. Pfeifer; Eve Melanie Reiter; McKenna Hendrickson; Julie Dangremond Stanton (International Journal of STEM Education, 2020)
Abstract Background Students with disabilities are underrepresented in undergraduate science, technology, engineering, and mathematics (STEM) courses. Students with disabilities who engage in self-advocacy earn higher GPAs and are more likely to graduate from college compared to students with disabilities who do not engage in self-advocacy. We utilized Test’s conceptual framework of self-advocacy, which breaks self-advocacy into four components: knowledge of self, knowledge of rights, communication, and leadership to investigate how students with invisible disabilities practice self-advocacy in undergraduate STEM courses. Through a partnership with a disability resource center (DRC), we recruited and interviewed 25 STEM majors who received accommodations for attention-deficit/hyperactivity disorder (ADHD) and/or a specific learning disorder (SLD). Data were collected using semi-structured interviews and analyzed using content analysis. Results We found evidence of all components of Test’s conceptual framework of self-advocacy and operationalize each based on our participants’ experiences. We identified novel components of self-advocacy for students with ADHD/SLD in undergraduate STEM courses, including knowledge of STEM learning contexts and knowledge of accommodations and the process to obtain them, as well as, a novel self-advocacy behavior, filling gaps. Filling gaps involved participants taking action to mitigate a perceived limitation in either their formal accommodations from the DRC or a perceived limitation in the instructional practices used in a STEM course. We also identified beliefs, such as view of disability and agency, which influenced the self-advocacy of our participants. We incorporated the emergent forms of self-advocacy into Test’s conceptual framework to propose a revised model of self-advocacy for students with ADHD/SLD in undergraduate STEM courses. Conclusions We developed a revised conceptual model of self-advocacy for students with ADHD/SLD in undergraduate STEM courses. This conceptual model provides a foundation for researchers who wish to study self-advocacy in undergraduate STEM courses for students with ADHD/SLD in the future. It also offers insights for STEM instructors and service providers about the self-advocacy experiences of students with ADHD/SLD in undergraduate STEM courses. We propose hypotheses for additional study based on our conceptual model of self-advocacy. Implications for research and teaching are discussed.